PWE-047 Improved patient-reported outcomes with upadacitinib over 52 weeks in patients with moderate-to-severe crohn's disease. (June 2019) - Peyrin-Biroulet, L; Louis, E; Loftus, EV; Lee, WJ; Cataldi, F; Lacerda, A; Ghosh, S
Abstract : Introduction: Upadacitinib (UPA), a selective JAK1 inhibitor was associated with clinical and endoscopic efficacy over 52 weeks (wks) in patients with moderate–to-severe refractory Crohn's disease (CD) (Sandborn, 2017). This is the first study assessing the long-term effects of UPA on patient-reported outcomes (PROs) in CD. Methods: 52 wk data from the phase 2 CELEST study were analysed for long-term effects of 4 UPA regimens on PROs. Patients (pts) who completed the 16 wk induction period were re-randomised 1:1:1 to receive UPA 3 mg twice daily (BID), 12 mg BID or 24 mg daily (QD) for 36 wks. The 24 mg QD arm was later stopped and a 6 mg BID arm initiated to evaluate an intermediate maintenance dose. Pts completed the Inflammatory Bowel Disease Questionnaire (IBDQ), EuroQol (EQ-5D) and Work Productivity and Activity Impairment (WPAI) PROs at baseline, wk 16, and wk 52. Wk 52 outcomes for pts who received UPA induction therapy and achieved clinical response at wk 16 were assessed. Percentages of pts achieving IBDQ response (minimum clinically important differences ≥16-point increase in IBDQ from baseline) and IBDQ remission (IBDQ ≥170) at wk 52 were determined using non-responder imputation (NRI). Changes from baseline to wk 52 were calculated using observed cases (OC) and analysis of covariance for IBDQ, EQ-5D visual analogue score (VAS) and WPAI. Results: Among 94 wk-16 clinical responders, a greater proportion of pts in the BID dose groups attained IBDQ response and achieved IBDQ remission at wk 52 than those in the 24 mg QD dose group (table 1 ). Dose-related improvements in mean IBDQ and EQ-5D VAS were observed in the 3 mg, 6 mg and 12 mg BID dose groups at wk 52. At wk 52, improvements in WPAI including reduction of activity impairment and work impairment were numerically greater for the BID dose groups. Conclusions: Maintenance treatment with UPA among wk-16 clinical responders resulted in improved quality of life based on IBDQ, EQ-5D and work productivity over 52 wks. Numerically greater improvements were reported in the pts who received 12 mg BID. Reference: Sandborn WJ, et al. Gastroenterology. 2017;152(5) Suppl 1:S1308–S1309